Evitando o encontro dos corpos: audiência de custódia em Guarulhos durante a pandemia - Cinquini, Bruna (Universidade Federal de São Carlos, 2023)
This research focuses on custody hearings during the pandemic. Custody hearings aim to ensure the fundamental rights of the detainee, but with the Covid-19 pandemic, hearings were suspended and the discussion about conducting them via videoconference resumed. Given this situation, the general objective of this research is to analyze the public debate regarding the necessary adaptations for the functioning of custody hearings in the context of the Covid-19 pandemic, regarding access to justice and the fundamental rights of the detainee. Specifically, the research sought to a) map the situation of custody hearings during the Covid-19 pandemic; b) analyze the impacts of Recommendation No. 62 on judicial appreciation in cases of detainees in the Judicial Circuit of Guarulhos; c) understand the representations of key actors and operators in the management of the pandemic in the judiciary regarding the balance between sanitary safety and fundamental rights; d) conduct a survey of arguments and justifications mobilized in the public debate about the conducting of custody hearings via videoconference before and during the Covid-19 pandemic. The hypothesis is that there is a reconfiguration of the very objectives of custody hearings to ensure the sanitary safety of legal operators at the expense of the detainee. Using mixed methods, quantitative analysis was carried out through data from the Custody Hearing System (SISTAC) and the São Paulo Court of Justice (TJSP). Qualitative data was constructed through a literature review, interviews with justice system actors, official documents analysis, news and legal media. Based on the data analysis, it was possible to verify that the pandemic and Recommendation No. 62 of the National Council of Justice (CNJ) did not impact the decisions of judges. It was also found that the defense of virtual format did not have sanitary safety as its main argument, but productivity. The justifications for the defense of videoconference are similar to those before the pandemic, emphasizing productivity. Even with all the disputes, aggravated by the pandemic and under punitive governments, custody hearings managed to produce tensions, showing that the state field of conflict administration is not only dominated by one logic, but has ambivalent views coexisting and conflicting.
Avoiding physical encounters: custody hearings in Guarulhos during the pandemic
Keywords: Audiência de custódia; Justiça criminal; Controle do crime; Sociologia da punição; Sociologia da violência; Custody hearing; Criminal justice; Crime control; Sociology of punishment; Sociology of violence; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS